MENINGKATKAN HASIL BELAJAR KOGNITIF MAHAHASISWA CALON GURU BERKEMAMPUAN AKADEMIK BAWAH DENGAN MODEL PEMBELAJARAN RQA - Wulandari Saputri (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
Abstract One of the crucial element should be mastered by prospective teacher-students is the content of the material. A low score cognitive learning outcomes can adversely affect future teaching careers. The academic ability factor is believed to be influential in this regard. Applying the right learning model can be the solution. This study aimed to determine the increase in cognitive learning outcomes of pre-service teachers with lower academic abilities after using the RQA learning model. This quasi-experimental research with pretest-posttest nonequivalent control group design involved pre-service of Biology Education Study Program Universitas Muhammadiyah Palembang as research samples. The research instrument was in the form of an essay test, and its rubric and the results were analyzed using ANCOVA. The research finding that the pre-service teachers who have the lower academic ability who taught by using RQA learning model got an average score of cognitive learning outcomes that were higher than pre-service teacher who have high academic ability who taught by using conventional learning. Thus, RQA can be used as a powerful alternative learning model to improving cognitive learning outcomes of pre-service teacher. Keywords : academik ability, cognitive learning outcome, RQA learning model, pre-service teacher, teacher education